2004
DOI: 10.1525/si.2004.27.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Contesting Stigma: On Goffman's Assumptions of Normative Order

Abstract: Goffman's classic analysis of stigma tacitly suggests that it has a conditional nature. An important shortcoming, however, is that his analysis proceeds from the existence of a normatively shared understanding of the criteria for and the distribution of stigma assignment. I use data from Somali immigrants to Canada to further that argument by showing that stigma as a social object cannot be created when its cultural and structural contexts are disjunctive. Through reverse stigmatization, counter devaluation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 34 publications
4
80
0
Order By: Relevance
“…Goffman's work clearly resonates in many areas of research and Link and Phelan (2001) provide an impressive overview of the different contexts in which the concept has been used. Much of this literature has focused on the way these stigmatised groups manage their relationships with the society in which they reside or their rejection by that society (Field 1994;Kusow 2001Kusow , 2004.…”
Section: Stigma and Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Goffman's work clearly resonates in many areas of research and Link and Phelan (2001) provide an impressive overview of the different contexts in which the concept has been used. Much of this literature has focused on the way these stigmatised groups manage their relationships with the society in which they reside or their rejection by that society (Field 1994;Kusow 2001Kusow , 2004.…”
Section: Stigma and Migrationmentioning
confidence: 99%
“…These are criticised as some of the worse types of leaders: those who have returned to benefit financially and take the money out of the country, to finance their other Western lives. In a form of stigma reversal (Kusow 2004), their experience of life 'over there' is turned into a source of superiority over those who accept how life is 'over here'. There is a disdain for the country of origin, for the society, for way of life and traditions.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…A study among a sample of Somali immigrants in Canada raises the counterintuitive possibility of 'reverse stigmatization' and 'counter devaluation' of stigmatizers by the stigmatized. 35 Furthermore, not all people who are concerned about public stigma self-stigmatize. The risk factors for self-stigmatization, in particular, are not adequately explored in adult literature.…”
Section: The Dimensions Of Stigmamentioning
confidence: 99%
“…Waxman 1977, p. 91), but other studies showed a vast range of strategies. Kusow (2004) asked how Somali immigrants in Toronto react to dominant color-based stigma. He shows that through reverse stigmatization, counter devaluation, and rejection of discrimination, Somalis reveal the problematic of stigma establishment.…”
Section: The Internal Differentiation Of Neighborhoodsmentioning
confidence: 99%